2003
DOI: 10.1093/aob/mcg098
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Jasmonic Acid Induces Changes in Apical Meristem Morphology of Potato Stolons

Abstract: Hooked apex stolons and initial swelling stolons of potato plants were treated with 3 x 10-8 mol l-1 jasmonic acid (JA) to study the effect of this compound on histology, cell expansion and tissue differentiation. In hooked apex stolons, JA application increased the meristem thickness and reduced the length of the leaf primordia, whereas in initial swelling stolons narrowing of the apical region, absence of leaf primordia and swelling of the subapical meristem were evident. Early vascular tissue differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 6 publications
4
43
0
Order By: Relevance
“…Interestingly, an earlier developmental expression pattern occurred after MeJA treatment, as shown by the appearance of GUS staining in a location closest to the root tip, suggesting a role of AtAO1 in MeJA signaling leading to protoxylem differentiation. In a few recent reports, a still quite unexplored role for MeJA in xylem development was suggested (Cenzano et al, 2003;Fattorini et al, 2009). In this regard, exogenous JA and MeJA have been shown to induce early xylem differentiation in potato stolons (Cenzano et al, 2003) and xylogenesis in tobacco thin cell layers (Fattorini et al, 2009), respectively.…”
Section: Atao1-overexpressing Plants Show Early Protoxylem Differentimentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, an earlier developmental expression pattern occurred after MeJA treatment, as shown by the appearance of GUS staining in a location closest to the root tip, suggesting a role of AtAO1 in MeJA signaling leading to protoxylem differentiation. In a few recent reports, a still quite unexplored role for MeJA in xylem development was suggested (Cenzano et al, 2003;Fattorini et al, 2009). In this regard, exogenous JA and MeJA have been shown to induce early xylem differentiation in potato stolons (Cenzano et al, 2003) and xylogenesis in tobacco thin cell layers (Fattorini et al, 2009), respectively.…”
Section: Atao1-overexpressing Plants Show Early Protoxylem Differentimentioning
confidence: 99%
“…In a few recent reports, a still quite unexplored role for MeJA in xylem development was suggested (Cenzano et al, 2003;Fattorini et al, 2009). In this regard, exogenous JA and MeJA have been shown to induce early xylem differentiation in potato stolons (Cenzano et al, 2003) and xylogenesis in tobacco thin cell layers (Fattorini et al, 2009), respectively. This work reveals that MeJA treatment results in early protoxylem differentiation in Arabidopsis wild-type seedlings ( Fig.…”
Section: Atao1-overexpressing Plants Show Early Protoxylem Differentimentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggests that high concentrations of JA (1.0 mg·L -1 ) resulting in an increase in the dry matter (%) of plantlets, whereas shorter plantlets with less branched shoots & roots of plantlets showed decreased fresh weight using a higher concentration (Zhang et al 2006). Takahashi et al (1994) and Cenzano et al (2003) suggested that the observed microtuber formation in the presence of JA could be due to increased cell expansion, a reduction in the length of leaf primordia, enlargement of meristems, and early vascular tissue differentiation. However, Vilhar et al (1997) suggested that JA supplementation altered morphology of roots through cell division and inhibited root elongation.…”
Section: Dry Weight Of Plantletsmentioning
confidence: 99%